Upaya Pemerintah terhadap Penanggulangan Kejahatan Penyelundupan Satwa Liar Dilindungi Melalui Jalur Wilayah Perairan Indonesia - Dinda Hafidzah; Antonius Reiyhand Nathaniel Matahelumual; Elsa Aprina (Lex Renaissance, 2022)
This study aims to determine the government’s attempt to address the criminal action of smuggling the protected wildlife that occurs through Indonesian territorial waters. Indonesia’s nature which is touted as Mega-Biodiversity by the world is not immune from smuggling crimes which lead to illegal trade of protected wild animals. Not infrequently, this particular illegal activity is carried out by sea as one of the trade route. With the development of modes and cases of smuggling crimes that threaten the survival of protected wildlife, this raises the question of what efforts can be made by the government in handling the crime of smuggling protected wildlife through Indonesian territorial waters. This is a normative juridical research by using statutory approach. This study concludes that in dealing with the development of criminal modes in smuggling which often increase the number of cases, the government has taken preventive measures in the form of issuing laws, establishing supervisory bodies and international scale cooperation as well as repressive efforts in the form of imposing sanctions on perpetrators who have caught in the course of smuggling.Keywords: Crime Prevention, Wildlife Smuggling, Indonesian waters. AbstrakPenelitian ini bertujuan untuk mengetahui upaya pemerintah dalam menanggulangi kejahatan penyelundupan satwa liar dilindungi yang terjadi melalui wilayah perairan Indonesia. Alam Indonesia yang disebut-sebut sebagai Mega-Biodiversity oleh dunia pun tidak luput dari kejahatan penyelundupan yang berujung pada perdagangan ilegal terhadap satwa liar dilindungi. Tak jarang, kegiatan ilegal ini dilaksanakan melalui laut sebagai jalur perdagangannya. Dengan berkembangnya modus dan kasus kejahatan penyelundupan yang mengancam keberlangsungan hidup satwa liar dilindungi ini pun memunculkan pertanyaan soal bagaimanakah upaya yang dapat dilakukan oleh pemerintah dalam menanggulangi kejahatan penyelundupan satwa liar dilindungi melalui jalur wilayah perairan Indonesia. Penelitian ini merupakan penelitian hukum yuridis normatif dengan menggunakan pendekatan perundang-undangan. Kesimpulan dari penelitian ini adalah bahwa dalam menghadapi perkembangan modus kejahatan penyelundupan yang kerap meningkatkan jumlah kasus, pemerintah telah melakukan upaya preventif berupa penerbitan hukum, pembentukan badan-badan pengawas serta kerja sama berskala internasional dan juga upaya represif dalam bentuk pemberian sanksi terhadap para pelaku yang telah tertangkap dalam berlangsungnya penyelundupan.Kata-kata Kunci: Penanggulangan Kejahatan, Penyelundupan Satwa Liar, Perairan Indonesia.